2019
DOI: 10.4018/ijeis.2019070102
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Adoption of Cloud-Based ERP of Nigerian's SMES Manufacturing Sector Using Toe Framework and Doi Theory

Abstract: Adoption factors relating to enterprise resource planning (ERP) have been studied quite extensively over the years. Most of the earlier studies on cloud ERP have focused only on technical and operational issues. A few studies have addressed the adoption of cloud ERP from the user's perspective, mostly assessing the effects of the innovation characteristics or the contextual factors. Very few studies to date have conducted a holistic evaluation of both the direct and indirect effects of the determinants on clou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 36 publications
8
31
0
Order By: Relevance
“…In other words, the third hypothesis is accepted. The result is consistent with previous study [2,5,[18][19] which showed that external pressure was an important factor that positively influencing the acceptance of technologies in MSMEs. External pressure in this paper includes competitors, partners and customers, as well as the role of government.…”
Section: Hypothesis Testingsupporting
confidence: 92%
“…In other words, the third hypothesis is accepted. The result is consistent with previous study [2,5,[18][19] which showed that external pressure was an important factor that positively influencing the acceptance of technologies in MSMEs. External pressure in this paper includes competitors, partners and customers, as well as the role of government.…”
Section: Hypothesis Testingsupporting
confidence: 92%
“…The framework examines three important factors that influence the adoption of new technologies: technology, organization, and environment [41]. The TOE framework has been widely utilized to research the adoption of cloud-based ERP [5][6][7][8][9][10][11][12][13][14][15] and cloud computing [42]. Juiz et al [43] used the TOE framework for SaaS ERP adoption by SMEs, and explored perceived value, security concerns, configurability and customization, organizational readiness, top management, competitive pressure, and vendor qualities.…”
Section: Technology-organization-environment (Toe) Frameworkmentioning
confidence: 99%
“…A survey was conducted to verify the research model. The measured items regarding TOE and innovation characteristics were selected from prior studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]24,35,[40][41][42][43][44][45][46]. In addition, the measured items regarding resistance characteristics were selected from revisions of existing items to better fit the research context [3,13,[21][22][23]38,[47][48][49][50][51][76][77][78][79][80][81][82][83].…”
Section: Measurementsmentioning
confidence: 99%
See 2 more Smart Citations